'Keep people safe': Designing a participatory performance within the strict parameters of social distancing in Australia. Issue 1 (6th March 2023) - Fahd, Cherine
This article recounts designing and performing an intimate encounter with strangers during the pandemic. At the end of 2020, as Australians emerged from a long period of 'lockdown', the celebrated Sydney Opera House again opened its doors to the public. Commissioned to create a new work for the Sydney Opera House's Antidote Festival, I designed a 'touch' performance that met the Australian Government's COVID-19 protocols for social distancing at indoor events. Instead of being frustrated by the restrictions, I used the health and safety rules as if they were conceptual instructions. Surprisingly, I was reminded of the 1960s and 1970s conceptual artists whose experimental capacity was borne from instructive limitations. Seeing the restrictions as an opportunity, I discuss how the physical limitations ushered in by COVID-19 (along with the heritage status of the Sydney Opera House) provided the parameters for conceiving a scene and an experience that was everything the pandemic denied – public, participatory, intimate and physical. I also reflect on what I learned in the process and how needing to keep people safe brought profound ethical understanding.